Euthanasia as privileged compassion - Buijsen, M. A. J. M., 1963- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2024)
This Element overviews developments and issues in Dutch euthanasia practice. Following an outline of the history of the Dutch Euthanasia Act and a survey of the most critical trends and figures, some current issues are explored in depth: euthanasia and incompetency, euthanasia by nonphysicians, and euthanasia for those who consider their lives completed. This Element is intended for a general readership, including undergraduate students in law, medicine, or ethics. This title is also available as Open Access on Cambridge Core.
The Euthanasia Act and Its Genesis -- Trends in Dutch Euthanasia Practice -- Euthanasia for the Incompetent -- Euthanasia by Non-physicians -- Age-related Conditions -- Concluding Remarks.
Title from publisher's bibliographic system (viewed on 17 May 2024).
Keywords: Euthanasia -- Netherlands -- History; Euthanasia -- Law and legislation -- Netherlands